Efektifitas Layanan Konseling Kelompok Dengan Pendekatan Realita Untuk Mengurangi Perilaku Membolos Siswa Kelas XI Di SMAN 1 Sikur - Devi Aprilia; Baiq Mahyatun; Dewi Yulianti (EDUCARE: Jurnal Pendidikan dan Kesehatan, 2026)
Truancy is a form of disciplinary violation that can hinder the learning process and reduce students' academic responsibility. This study aims to determine the effectiveness of group counseling services with a reality approach in reducing truancy behavior in eleventh grade students of SMURP-2 at SMA Negeri 1 Sikur in the 2025/2026 Academic Year. This study used a quantitative method with a Pre-Experimental Design, One Group Pretest-Posttest Design. The study sample consisted of 8 students selected using a purposive sampling technique. Data collection was conducted using a truancy behavior questionnaire, while data analysis used a Paired Sample t-Test with the help of IBM SPSS Statistics 25. The results showed that the average pre-test score of 92 (high category) decreased to 72 (moderate category) in the post-test. The results of the hypothesis test obtained a Sig. (2-tailed) value of 0.000 < 0.05, so H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that group counseling services with a reality approach were effective in reducing truancy behavior of the eleventh grade students of SMURP-2 SMA Negeri 1 Sikur in the 2025/2026 academic year.